Oncogenic Potential and Clinical Implications of Giant Endometrial Polyps: A Case Report and Literature Review - Brittany van Staalduinen; Andrew Stahler; Catherine Abied; Rita Shats; Nisha A. Lakhi (Case Reports in Obstetrics and Gynecology)
Endometrial polyps exceeding 4 centimeters in length are exceedingly rare and are termed “giant polyps.” We describe two patients that presented to our hospital with giant endometrial polyps. Clinical implications and oncologic potential of giant endometrial polyps are discussed. Risk factors of oncologic transformation include advanced age, menopausal status, obesity, diabetes, arterial hypertension, use of tamoxifen, and size greater than 1.0 centimeter. A literature review of all documented cases of giant endometrial polyps is presented and management strategies for counseling and polypectomy are reviewed.